Predictors of sustainment of two distinct nutrition and physical activity programs in early care and education - Swindle, Taren; Bellows, Laura L.; Mitchell, Virginia; Johnson, Susan L.; Shakya, Samjhana; Zhang, Dong; Selig, James P.; Whiteside-Mansell, Leanne; Curran, Geoffrey M. (Frontiers in Health Services, 2022)
Introduction The goal of the present study was to investigate factors associated with sustainment of two evidence-based programs for nutrition promotion in early care and education (ECE) settings – Food Friends (FF) and Together, We Inspire Smart Eating (WISE). Materials and methods In a cross-sectional study design, ECE directors (N = 55) from centers that had previously been trained in WISE or FF completed a survey. Program-specific measures included Steckler's Perception of Innovations, the Program Sustainability Assessment Tool (PSAT), and the Organizational Readiness for Change Assessment (ORCA). For our primary outcomes, two measures of sustainment were examined: Nutrition Continued Practice (i.e., the use of or general focus on nutrition programs) and Program Fidelity (i.e., how well centers used specific evidence-based practices of WISE or FF). Multiple regression was used to determine the association of these outcomes with program, years since last implementation, and overall scores on predictors. Follow-up correlation analyses were used to investigate outcome relationships with context submeasures due to high intercorrelations between predictor submeasures. Results Nutrition Continued Practice was significantly predicted by program and overall PSAT score. WISE programs had significantly higher Nutrition Continued Practice scores than FF program (p = 0.03). All subscales of the PSAT (e.g., environmental support, funding stability, organizational capacity, program adaptation, communications, and strategic planning) were significantly correlated with Nutrition Continued Practice (all rs > 0.30, all ps < 0.03). Program Fidelity was significantly predicted by PSAT and Steckler Perception of Innovation scores. All subscales of the PSAT were strongly positively correlated with Program Fidelity (all rs > 0.48, all ps < 0.001); relative advantage (r = 0.54, p < 0.001) and level of institutionalization (r = 0.61, p < 0.001) were positively correlated with Program Fidelity. Conclusion This study suggests that factors associated with the continued practice of program principles are partially distinct from those that are associated with the sustainment of specific practices driving program fidelity. Results suggest capacity building strategies may be important for both continued attention to nutrition and physical activity as well as sustaining fidelity to specific evidence-based practices.